Heart rate and blood lactate concentrations as predictors of physiological load on elite soccer players during various soccer training activities - Eniseler, N. (The Journal of Strength and Conditioning Research, 2005)
The purpose of this investigation was to estimate the physiologic strain on players during various soccer training activities. Ten soccer players from the first division soccer league of Turkey were used as subjects. The heart rate responses were measured during 4 types of soccer training. First, the heart rates that corresponded to a blood lactate concentration of both 2 and 4 mM were measured, and then, during the 4 types of training, they were correlated with the proportion of time that the heart rate was below the 2-mM lactate line, between the 2- and 4-mM lactate lines, and above the 4-mM lactate line. Mean heart rates during friendly match, modified game, tactical training, and technical training activities were 157 ± 19, 135 ± 28, 126 ± 21, and 118 ± 21 b·min?1, respectively. The differences between all of these soccer training activities were statistically significant (p 0.01). The results demonstrate that (a) technical and tactical training consisted of very low exercise intensities (most of the heart rates were below the 4-mM lactate level) and (b) the percentages of time that the heart rate correlated to a point above the 4-mM lactate reference level during the friendly match and modified game were 49.6 ± 27.1% and 23.9 ± 24.5%, respectively. The practical implications of these findings are that, by using 2- to 4-mM reference lines, coaches can structure heart rate zones that can help determine the individualized exercise intensity for their players as well as estimate overall exercise intensity during soccer training.